(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Objectives Effectiveness of Mulligan Mobilization in Frozen ShoulderDesign Randomized Control TrialMethodology According to predetermined inclusion and exclusion criteria, a total of 30 patients wereenrolled. They were then randomly divided into two groups, each of which had 15 patients. While GroupB received ultrasound treatment combined with exercises (stretching, strengthening, and ROMexercises) three times per week for four weeks, Group A had Mulligan mobilization in addition to theseactivities (12 sessions). The visual analog scale, the Shoulder Pain and Disability Index (SPADI), andgoniometry for Shoulder Range of Motion were used to evaluate the patient’s outcomes. Values frombefore and after the therapy were kept in order to compare the outcomes.ResultsThis research demonstrated that the patient’s range of motion in external rotation, abduction, andflexion, as well as the degree of their pain, had significantly improved.Conclusion The study’s findings imply that Mulligan and ultrasound may both help with frozen shoulderissues. Mulligan group had more improvement than Ultrasound group. Based on these findings, Mulliganmobilization with exercises, as opposed to ultrasound with exercises, should be the preferred method oftherapy for frozen shoulder.